2011
DOI: 10.3390/ma4122197
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Degradation Behavior of the Magnesium Alloy LANd442 in Rabbit Tibiae

Abstract: In former studies the magnesium alloy LAE442 showed promising in vivo degradation behavior and biocompatibility. However, reproducibility might be enhanced by replacement of the rare earth composition metal “E” by only a single rare earth element. Therefore, it was the aim of this study to examine whether the substitution of “E” by neodymium (“Nd”) had an influence on the in vivo degradation rate. LANd442 implants were inserted into rabbit tibiae and rabbits were euthanized after 4, 8, 13 and 26 weeks postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 52 publications
(116 reference statements)
2
33
0
Order By: Relevance
“…The volume of the calculated implant parts seems to decrease over time while the density showed a slight increase after 24 weeks. Also Ullmann et al [86] found no significant changes in LANd442 implant volume but a significant decrease in density after 26 weeks. Additionally, they reported a significant decrease in maximum force as corrosion magnesium usually undergoes if exposed to chloride ions in nonoxidizing solutions [87] and was observed by several authors examining different magnesium-based alloys in vivo [44] or in vitro [88].…”
Section: Discussionmentioning
confidence: 95%
“…The volume of the calculated implant parts seems to decrease over time while the density showed a slight increase after 24 weeks. Also Ullmann et al [86] found no significant changes in LANd442 implant volume but a significant decrease in density after 26 weeks. Additionally, they reported a significant decrease in maximum force as corrosion magnesium usually undergoes if exposed to chloride ions in nonoxidizing solutions [87] and was observed by several authors examining different magnesium-based alloys in vivo [44] or in vitro [88].…”
Section: Discussionmentioning
confidence: 95%
“…Using a three‐point bending test of pins with the same geometry (diameter: 2.5 mm, length: 25 mm), the mechanical stability (maximal force F max ) was highest for the LAE442 alloy (255.67 N), followed by ZEK100 (240.79 N), and WE43 (238.05 N) . The alloys MgCa0.8 (178.76 N), AX30 (177.42 N), and LANd442 (194.5 N) have low initial stability. Three months after in vivo implantation, the mechanical stability of these magnesium alloys was further reduced by 30–50% .…”
Section: Biomechanical Stability Of Degradable Metal Biomaterialsmentioning
confidence: 99%
“…It displays the homogeneity of the overall degradation of an implant. 3,22 The implant's corrosion rate was calculated using the in vivo mCT data according to the following formula: CR = DV/(A 3 t). 23 Here, CR (mm/year) is the corrosion rate, DV (mm 3 ) is the volume loss, A (mm 2 ) is the area that was exposed to the corrosion and t (days) is the implantation period.…”
Section: Animal Modelmentioning
confidence: 99%